(untitled) (Third Sector Social Economic Review, 2022)
Selection problems are one of the types of problems that are often encountered from the point of view of companies and are difficult to decide. The reason it is a difficult problem is that many criteria and alternatives must be considered at the same time. Multi-criteria decision-making approaches are often used to solve these problems. Selection problems can vary a lot because they are faced at every stage of life. In this study, the selection process of enterprise resource planning (ERP) is discussed. The purchasing department of a company that wants to buy new software has set many criteria and alternative software. It is planned to select alternative software where these criteria are met at the most appropriate level. For the solution to this problem, the fuzzy Entropy method was used at the stage of determining the criterion weights. In the process of evaluating software alternatives, the fuzzy Multi-Objective Optimization by Ratio Analysis (MOORA) method was used, and the most appropriate software was decided. As a result of the study, it was found that the third software system was the most suitable of the three software systems identified.